Protolysis Reaction on Pyrophyllite Surface Molecular Models: A DFT Study - Bentabol-Manzanares, María José; Pérez del Valle, Carlos; Hernández Laguna, Alfonso; Huertas, F. Javier (MDPI, 2025)
Understanding the mechanisms of mineral dissolution at the atomic scale is crucial for interpreting geochemical processes in soils and sediments, particularly those involving clay minerals. This study addresses the dissolution of pyrophyllite, a model dioctahedral phyllosilicate, under acidic conditions by employing Density Functional Theory (DFT) to simulate protolysis reactions at four distinct edge surfaces ({100}, {010}, {110}, and {130}). Molecular cluster models were constructed for each edge, and the interactions of protons and hydronium ions with various oxygen sites were systematically analyzed. The results demonstrate that bridge oxygens, especially those coordinated to one silicon and two aluminum atoms, are the most reactive sites, undergoing significant bond breaking and structural distortion upon protonation, while hydroxyl groups mainly accommodate structural changes without initiating dissolution. The {110} edge was found to be the least reactive, whereas the {100}, {010}, and {130} edges exhibited the highest reactivity. Hydronium ions produced similar or greater structural changes compared to protons, with water molecules forming hydrogen bonds with the resulting structures. These findings confirm that protonation of bridge oxygens is the rate-limiting step in phyllosilicate dissolution, and that octahedral cations are released preferentially over tetrahedral ones. These findings are consistent with the conclusions drawn from the dissolution experiments. This study provides atomistic information on the dissolution mechanisms of clay minerals at a scale that exceeds the capabilities of dissolution experiments, emphasizing the importance of edge reactivity relative to extensive basal surfaces and the role of water in proton transfer and facilitating protolysis reactions.
Keywords: Pirofilita - Aspectos moleculares; Química organometálica; DFT; Pyrophyllite; Molecular surface models; Protolysis reaction models; Acid dissolution mechanism; Surface reactivity